EARNINGS QUALITY IN HEALTHCARE FIRMS: THE MODERATING ROLE OF AUDIT DELAY AND THE MEDIATING EFFECT OF TAX AGGRESSIVENESS - Mohamad Zulman Hakim; Aulia Imelda; Nahwa Nikhuatun; Putri Yuningsih; Zahra Prada Devi Hasbilah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to examine the effect of company size, profitability, audit committee, and company risk on earnings quality with audit delay as a moderating variable and tax aggressiveness as a mediating variable in healthcare companies listed on the IDX for the period 2021–2024. The research sample consisted of 11 companies with 44 firm-year observations selected using purposive sampling. Secondary data were processed using FEM and REM panel data regression using EViews 12 and Sobel and Process Macro Hayes Model 7 tests for moderated mediation. The results show that company size (p = 0.0004; β = 0.285) and audit committee (p = 0.0493; β = 2314.675) have a significant positive effect, while company risk (p = 0.0119; β = –0.446) has a significant negative effect on earnings quality, while profitability is not significant (p = 0.9429). Audit delay significantly moderates the relationship between company size (p = 0.0367), audit committee (p = 0.0420), and company risk (p = 0.0228) on earnings quality, but does not moderate profitability (p = 0.6892). Tax aggressiveness (CETR) was found to significantly mediate the relationship between company size (Sobel = 6.95) and company risk (Sobel = 7.65) on earnings quality, but did not mediate profitability and audit committee. The moderated mediation test showed a significant index on all combination paths (p < 0.05). This study provides the first empirical evidence in the Indonesian healthcare sector post-pandemic that audit delay and tax aggressiveness are critical mechanisms for the decline in earnings quality, so regulators (OJK) and investors need to tighten their supervision of timely audits and tax avoidance practices at hospital and pharmaceutical issuers.